Antibacterial Activity Test of Bacteriocin from Lactobacillus brevis, Lactobacillus casei and Lactobacillus plantarum Against Gram Positive Pathogenic Bacteria - Novi Permata Sari; Rafika Sari; Eka Kartika Untari (Journal of Tropical Biodiversity and Biotechnology, 2018)
Bacteriocin is a secondary metabolite product of lactic acid bacteria (LAB) which have an antimicrobial and potentially as a natural preservative. LAB isolates used in this study were Lactobacillus brevis, Lactobacillus casei and Lactobacillus plantarum. This study aimed to determine the antibacterial activity of bacteriocin produced by each isolate of LAB including the influence of pH and heating variation against Bacillus cereus, Bacillus subtilis and Staphylococcus epidermidis. Antibacterial activity test was done by using disc diffusion method. method. Confirmation test using proteolytic enzyme aimed to analyse that the inhibition zone produced from the activity of bacteriocin. The inhibition zone produced from L. brevis, L. casei and L. plantarum against B. cereus were 15.70, 16.43 and 14.50 mm, against B. subtilis were 13.37, 14.10 and 12.53 mm and against S. epidermidis were 11.37, 14.50 and 12.45 mm. The activity of each bacteriocin decreased with the addition of trypsin and catalase, bacteriocin was active in the pH range of 2-10 and heating temperature of 40-121oC. Statistical test showed that the addition of trypsin, catalase and the variation of pH also heating had significant differences (p<0.05) to antibacterial activity produced by bacteriocin from L. brevis, L. casei and L. plantarum.